The Gender of the Apologiser as a Social Factor in the Selection of Apology Strategies: A Socio-pragmatic Study - Wathiq, Sahar; Shwaysh, Muslih (Al-Adab Journal, 2023)
"Politeness" is a culturally defined pattern of language use that enables the speaker to formulate appropriate speech acts like an apology. The speech act of apology is a part of pragmatics study and belongs to expressive speech acts. However, it cannot be separated from sociolinguistics because social factors such as social context, gender, and the participants’ relationship can all have an impact on how apologizers make their apologies. The selection of the appropriate formulas of apology strategies to pay off violations of social norms is considered a hard task since it is based on some cultural and social norms. Thus, the present study aims to study the apology strategies used by Iraqi male/female postgraduate students at the University of Anbar, in addition to investigating the effect of gender on the use of polite apology strategies. An oral Discourse Completion Task was used as a data collection instrument, supported by a semi-structured interview. The data has been analysed using the descriptive analysis method, based on Leech’s (2014) classification of apology. The findings revealed that "expressing regret" was the most frequently used apology strategy. Furthermore, both genders used different indirect strategies to support their apologies. Both genders used a new supporting move, which is "admitting responsibility for in-group member’s fault." In conclusion, the gender of the participants has a slight effect on the choice of polite apology strategies. Moreover, social status and age were the most effective social factors as compared to the others.